2015
DOI: 10.1016/j.jssc.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure powder x-ray diffraction study of EuVO4

Abstract: Abstract:The high-pressure structural behavior of europium orthovanadate has been studied using in-situ, synchrotron based, high-pressure x-ray powder diffraction technique. Angle-dispersive x-ray diffraction measurements were carried out at room temperature up to 34.7 GPa using a diamond-anvil cell, extending the pressure range reported in previous experiments. We confirmed the occurrence of zircon-scheelite phase transition at 6.8 GPa and the coexistence of low-and high-pressure phases up to 10.1GPa. In addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 55 publications
(115 reference statements)
9
52
1
Order By: Relevance
“…The equation of state has been determined for zircon and scheelite phases from the experiment, with values of the bulk modulus K 0 of 149 (6) GPa and 199(9) GPa for zircon and scheelite, respectively. In a recent M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 study, a similar result has been obtained using methanol-ethanol as pressure transmitting medium [14]; however, here the transition is reported to start at 6.8 GPa, and the phase coexistence is observed up to 10.1 GPa; the authors have observed that the x coordinate of the oxygen atom increases whereas the z coordinate decreases (both marginally, details not given).…”
Section: This Behavior Has Beensupporting
confidence: 65%
See 1 more Smart Citation
“…The equation of state has been determined for zircon and scheelite phases from the experiment, with values of the bulk modulus K 0 of 149 (6) GPa and 199(9) GPa for zircon and scheelite, respectively. In a recent M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 study, a similar result has been obtained using methanol-ethanol as pressure transmitting medium [14]; however, here the transition is reported to start at 6.8 GPa, and the phase coexistence is observed up to 10.1 GPa; the authors have observed that the x coordinate of the oxygen atom increases whereas the z coordinate decreases (both marginally, details not given).…”
Section: This Behavior Has Beensupporting
confidence: 65%
“…The volume collapse, │∆V│/V 0, at the zircon-toscheelite transition pressure is 10.7%, being close to the collapse value of 10% reported in Refs. [11] and [14] for the same material. The existing data on bulk moduli for the zircon-type and scheelite-type phases are summarized in Tables 3 and 4, whereas the variations with pressure of the bulk moduli and their derivatives observed in our experiment are displayed in Fig.…”
Section: Experimental Results On the Structure And Eos Of Euvomentioning
confidence: 99%
“…After these reports, systematic HP investigations followed on RVO4 compounds by various researchers, including the authors of this review [25,26,28,29,33,36,59,96,97]. Measurements on these compounds now have established beyond doubt that the RVO4 compounds with smaller ionic radii (Sm-Lu) transform from the zircon to the scheelite phase below 10 GPa with nearly 10 % volume discontinuity.…”
Section: X-ray Diffraction Experimentsmentioning
confidence: 99%
“…This is a common phenomenon observed in many compounds. 30,31 Therefore, only data measured under quasi-hydrostatic conditions should be used to determine the bulk modulus from compression studies. In our case, if only the results measured under non-hydrostatic conditions are fitted with a second-order EOS, B 0 ¼ 284(25) GPa is obtained.…”
Section: A Sample Characterizationmentioning
confidence: 99%